Meningkatkan Hasil Belajar Ekonomi/Akuntansi Siswa Melalui Pembelajaran Kooperatif Tipe Think Pair Share (TPS) di SMA Negeri 2 Aikmel - Baiq Evi Aprian Sutanti (Jurnal Paedagogy, 2021)
This study aims to improve the learning outcomes of economic / accounting students in class XII IPS using cooperative learning type Think Pair Share (TPS) at SMA Negeri 2 Aikmel. The research method used is classroom action research which is carried out in two cycles where each cycle consists of four stages of activity, namely (1) action planning, (2) action implementation, (3) action observation, and (4) action reflection. . The research subjects were 27 students of class XII IPS at SMA Negeri 2 Aikmel in which 18 male students and 9 female students. This study also involved accounting subject teachers as collaborators. Data collection techniques include observation, tests, documentation, and interviews. While the data analysis technique used qualitative and quantitative descriptive analysis. The results showed that the economic / accounting learning outcomes of students in class XII IPS experienced an increase through cooperative learning type TPS at SMA Negeri 2 Aikmel with several indicators including an increase in student activism by 14%, an increase in student activeness in participating in cooperative learning type TPS as much as 16% , an increase in student activity in pair / group discussions by 20%, an increase in learning completeness by 15%, and an increase in student activeness in discussions that is greater than other indicators such as activeness and completeness of student learning outcomes.